Safety of vaginal delivery among dichorionic diamniotic twins over 10 years in a UK teaching hospital. Issue 1 (3rd November 2016) - Rzyska, Ewelina; Ajay, Bini; Chandraharan, Edwin
Abstract: Objective: To determine whether vaginal delivery among dichorionic diamniotic twins remains a safe option following full implementation of the European Working Time Directive in the UK. Methods: A retrospective study was conducted using data for women with dichorionic diamniotic twin pregnancies who attended a teaching hospital in London, UK, for delivery between January 4, 2000, and December 23, 2010. Results: Among 892 women, 474 (53.1%) attempted vaginal delivery, 220 (46.4%) of whom achieved spontaneous vaginal delivery of both twins. Instrumental vaginal delivery was performed among 89 women (18.8%), and 165 (34.8%) women underwent emergency cesarean delivery. Delivery of the second twin by emergency cesarean (n=31) was predominantly for fetal distress (13 [41.9%]) or abnormal lie (10 [32.3%]). A 5‐minute Apgar score of 9 or 10 was recorded for 384 (83.7%) of 459 first twins and 369 (82.9%) of 445 second twins, irrespective of the mode of delivery. Conclusion: Vaginal delivery among dichorionic diamniotic twins had a good success rate and a low intrapartum emergency cesarean delivery rate. Training in cardiotocography and intrapartum procedures might further reduce the need for emergency cesarean delivery. Abstract : Vaginal delivery of dichorionic diamniotic twins was generally safe; however, training in internal podalic version and cardiotocography could further reduce need for emergency cesarean delivery.